Impact of mRNA-based vaccines in the prevention of adverse outcomes of COVID-19 infection in pregnancy: a single-center cohort study - Tudisco, Riccardo; Garufi, Cristina; Rizzo, Francesca; Polimeno, Teresa; Lanzone, Antonio; De Carolis, Sara (Frontiers in Pediatrics, 2023)
Several data have suggested that pregnant women have an increased risk of severe COVID-19 compared to those who are not pregnant. Moreover, different studies have showed that severe COVID-19 is limited mostly to unvaccinated women. The aim of the present study was to ascertain the different maternal and fetal outcomes in pregnant women with COVID-19 according to their vaccination status. A retrospective cohort study was carried out including all women admitted to the high-risk pregnancy unit of our center with COVID-19 between December 2021 and February 2022. Among the 163 women included in the study, 60 were vaccinated with an mRNA vaccine and 103 were unvaccinated. Pregnancy outcome and obstetrical and neonatal complications were encountered. Vaccinated women showed higher educational levels and lower prevalence of cases, with BMI >25 compared to unvaccinated women. Moreover, vaccinated women were admitted mostly for obstetrical indications rather than for COVID-related symptoms. In addition, the risk of developing COVID-19 pneumonia was significantly higher in unvaccinated women (p = 0.01) compared with vaccinated ones. Furthermore, pregnancy and neonatal outcomes showed some differences in the two cohorts. In unvaccinated women, the rate of C-section was higher (p = 0.03), and the mean birthweight percentile in their infants was impaired by COVID-19 infection (p = 0.01) when compared to those born to vaccinated women. Based on these results, we suggest that women who received a full course of vaccination were protected from the severity of the disease, having milder symptoms of SARS-Cov2 infection, while also presenting a more favorable pregnancy outcome.